OMBUDSMEN AS NATIONAL INSTITUTION FOR PROTECTION OF THE RIGHT TO EDUCATION IN UKRAINE - Melnychuk, Olga; Melnychuk, Maksym (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2018)
Under the conditions of an armed conflict in Eastern Ukraine the level of ensuring the fundamental human right to education is being reduced. Therefore there is a need to search for additional mechanisms of the protection of the right to education, among which must be singled out such an extra-judicial human rights mobile institution as an ombudsman. All this stipulates the purpose of the article: to find out the role of the Ukrainian Parliament Commissioner for Human Rights, the Commissioner of Ukraine on the rights of the Child and the Educational Ombudsman to ensure the right to education in Ukraine. During the study, such methods as the analysis of scientific literature, normative legal acts in the field of the right to education and annual reports of the Ukrainian Parliament Commissioner for Human Rights were used. The research results of the Razumkov Center (Ukraine) regarding the attitude of citizens to the Ukrainian Parliament Commissioner for Human Rightshave been analyzed. As a resultit was discovered that the measures taken by the Ukrainian Parliament Commissioner for Human Rights and the Commissioner on the rights of the Child for the right to education are active and effective. In the society the legislative introduction of the post of educational ombudsman as an additional human rights institution in the field of education in Ukraine is positively evaluated. The conducted study shows that subsidiary, non-judicial means of protection of the right to education in Ukraine have greater authority among Ukrainian citizens than the judicial system.